"Současná česká rodina" - dokumentace k datům - Kreidl, Martin (Masaryk University Press, 2023)
Title in English: "Contemporary Czech Family" - data documentation This is the source work of the "GGP - The Contemporary Czech Family" research project. The publication contains all the basic research data and basic analytical insights into the data. It summarizes the methodology of the research (the questionnaire, selection of respondents, and course of the field investigation, including methodological innovations). It empirically describes the basic distribution of variables and compares them with older data (and comparable data from other countries). It will be the essential reference guide for data users.